The Role of Information and Communication Technologies in the Training of Future Natural Science Teachers - Romanyshyna, Oksana; Lukashchuk, Valentina (Pedagogical Discourse, 2024)
The article examines the use of ICT in schools to implement the content of natural science education. ICT enables teachers to create conditions that foster students’ cognitive interest in natural science subjects. It is emphasized that a future natural science teacher must possess not only a high level of general culture and psychological-pedagogical competence but also approach problem-solving creatively and organize their activities on a creative basis. The use of ICT contributes to the development of pedagogical creativity among students of this specialty. These innovations serve as a means of intensifying the professional training process for future teachers by saving instructional time, expanding and deepening the scope of educational material, understanding the content of future professional activities, and rethinking the social and moral significance of the chosen profession. The integration of ICT into the professional training of future natural science teachers is identified as one of the key directions for modernizing the natural science education system, both in higher education institutions and general secondary education establishments. It is concluded that ICT in the training of future natural science teachers creates favorable conditions for implementing the core ideas of competency-based learning. This is achieved through ensuring individualization, technologization, innovation, humanization, and intensification of education. The foundation for using ICT in higher pedagogical and natural science education lies in the principles of person-centered and activity-based approaches. Moreover, students, during the learning process, do not merely acquire ready-made knowledge but actively construct it through professionally-oriented, creative educational activities. ICT creates conditions for the gradual formation of professional competencies in future natural science teachers, which serve as the basis for developing students’ creative abilities and methodological thinking. By creating ideal conditions for active cognitive activity, ICT promotes the realization of students’ intellectual potential in the process of forming the professional qualities of future natural science teachers.